Improving assessments of fuel treatment effects on surface fuels in ponderosa pine forests of the southern Rocky Mountains - Vakili, Emma, author; Hoffman, Chad, advisor; Dickinson, Yvette, committee member; Keane, Robert, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2015)
Fuel hazard reduction treatments have been widely employed in dry forests of the western United States in recent decades in response to the increasing extent and severity of wildfires. In order to design and accurately assess the effects of these fuel hazard reduction treatments, accurate fuel inventories are required. However, obtaining accurate assessments of fuelbeds is complicated by a lack of knowledge about the effects of treatments on surface fuels and their spatial distribution. This thesis focuses on enhancing knowledge of treatment effects on surface fuels in ponderosa pine sites across Colorado and New Mexico, USA. The primary emphasis is on Chapter 1, which focuses on the spatial distribution of surface fuels and how it is changed by fuel hazard reduction treatments. I found that total surface fuel loads were reduced by ~10% in thinned sites and ~50% in thinned and burned sites. Semivariance following thin and burn treatments was similar to untreated sites and lower than thin-only sites for all fuel components except 1,000-hr fuels, with fuel component semivariance being highly predictable (R2=0.99) from fuel component mean fuel loading. The scale of spatial independence for all fuel components and sites ranged from <1-50 m with the shortest spatial scales occurring for the finest fuel components (i.e. duff, litter, etc.). Mean fuel particle diameter strongly predicted (R2=0.88) the distance needed to achieve sample independence. Incorporating such knowledge of spatial variability into fuel sampling protocols will enhance assessment of wildlife habitat and fire behavior and effects modeling over singular stand-level means. Chapter 2 focuses on the physical characteristics of fuel particles present before and after fuel hazard reduction treatments. I report mean squared diameter (d2) values for downed dead woody surface fuels that can be used to improve fuel loading assessments using the widely applied planar intersect sampling protocol. The planar intersect method requires an approximation of the mean squared diameter (d2) of 1, 10, and 100-hr timelag size classes to create loading estimates for downed dead woody surface fuels. I analyzed woody surface fuels collected throughout the southern Rocky Mountains to create local d2 estimates for untreated, mechanically treated, and mechanically treated and broadcast burned sites. Resulting estimates were up to 38% higher in the 1- and 10-hr classes and 28% lower in the 100-hr classes when compared to previously published values from other regions. The new burned partially harvested values for 1- and 100- hour classes were also roughly 20% lower than in the other stand conditions.